Red-fleshed apple flavonoid extract alleviates CCl4-induced liver injury in mice - Chen, Yizhou; Wang, Yanbo; Jiang, Shenghui; Xu, Jihua; Wang, Bin; Sun, Xiaohong; Zhang, Yugang (Frontiers in Nutrition, 2023)
In recent years, the global incidence of liver damage has increased. Despite the many known health benefits of red-fleshed apple flavonoids, their potential liver-protective effects have not yet been investigated. In this study, we analyzed the composition of red-ﬂeshed apple flavonoid extract (RAFE) by high-performance liquid chromatography (HPLC). We then induced liver damage in mice with carbon tetrachloride (CCl4) and performed interventions with RAFE to analyze its effect on liver damage, using bifendate as a positive control. The results showed that catechin was the most abundant flavonoid in 'XJ4' RAFE (49.346 mg/100 g). In liver-injured mice, the liver coefficients converged to normal levels following RAFE intervention. Moreover, RAFE significantly reduced the enzymatic activity levels of glutamic oxaloacetic transaminase (ALT), glutamic alanine transaminase (AST), and alkaline phosphatase (ALP) in mouse serum. Furthermore, RAFE significantly increased the content or enzyme activity level of total glutathione, total antioxidant capacity, and superoxide dismutase, and significantly decreased the content of malondialdehyde in the liver of mice. In parallel, we performed histopathological observations of mouse livers for each group. The results showed that RAFE restored the pathological changes caused by CCl4 around the central hepatic vein in mice and resulted in tightly bound hepatocytes. The recovery effect of RAFE was dose-dependent in the liver tissue. Regarding intestinal microorganisms, we found that RAFE restored the microbial diversity in liver-injured mice, with a similar microbial composition in the RAFE intervention group and normal group. RAFE reduced the ratio of Firmicutes to Bacteroidetes, increased the levels of probiotic bacteria, such as Lactobacillus acidophilus, and Clostridium, and reduced the levels of harmful bacteria, such as Erysipelothrix Rosenbach. Therefore, RAFE ameliorated CCl4-induced liver damage by modulating the abundance and composition of intestinal microorganisms in mice. In conclusion, RAFE alleviated CCl4-induced liver damage in mice, with H-RAFE (5 mg·kg-1) significantly improving liver damage in mice but M-RAFE (1 mg·kg-1) significantly improving the imbalance of intestinal microorganisms in mice. Our research suggests that RAFE could be employed for the adjuvant treatment and prevention of liver damage, and may have important applications in food and medicine.